1999
DOI: 10.1190/1.1444639
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of electrokinetic conversions in fluid‐saturated borehole models

Abstract: Experimental and theoretical studies show that there are electromagnetic (EM) fields generated by seismic waves with two kinds of conversion mechanisms in a fluid‐saturated, porous medium. Within a homogeneous formation, the seismic wave generates a seismoelectric field that exists only in the area disturbed by the seismic wave and whose apparent velocity is that of the seismic wave. At an interface between differing formation properties, the generated seismoelectric wave is a propagating EM wave that can be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(55 citation statements)
references
References 19 publications
0
55
0
Order By: Relevance
“…[3][4][5][6][7] Furthermore, a wide range of field and laboratory validations of the coseismic field and the interface response was presented in the literature. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Several of these works compare either field measurements 15,17 or laboratory measurements 20 with a seismoelectric wave propagation model, corroborating that the coseismic and interface response fields are predicted by the theory.…”
Section: Introductionmentioning
confidence: 69%
“…[3][4][5][6][7] Furthermore, a wide range of field and laboratory validations of the coseismic field and the interface response was presented in the literature. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Several of these works compare either field measurements 15,17 or laboratory measurements 20 with a seismoelectric wave propagation model, corroborating that the coseismic and interface response fields are predicted by the theory.…”
Section: Introductionmentioning
confidence: 69%
“…From research based on this electrokinetic theory, one can distinguish two seismoelectric effects: (1) a coseismic (electric) field is coupled to seismic waves and therefore propagates with seismic wave velocity (e.g., Pride & Haartsen, 1996) and (2) a seismic wave that traverses an interface with a contrast in electrical or mechanical properties produces EM-waves that propagate outside the support of the seismic waves with much higher EM-wave speeds (e.g., Pride & Haartsen, 1996;Haartsen & Pride, 1997). These effects have been verified experimentally in the laboratory (e.g., Zhu et al, 1999Zhu et al, , 2000Zhu & Toksöz, 2003;Block & Harris, 2006;Bordes et al, 2006) and in the field (e.g., Long & Rivers, 1975;Butler et al, 1996;Mikhailov et al, 1997;Beamish, 1999;Garambois & Dietrich, 2001;Dupuis et al, 2007;Haines et al, 2007). Also, the coseismic magnetic fields associated with a Stoneley wave (Zhu & Toksöz, 2005) and with a shear wave have been measured (Bordes et al, 2006(Bordes et al, , 2008.…”
Section: Introductionmentioning
confidence: 84%
“…Full-waveform electroseismic simulations were performed by White & Zhou (2006); Hu et al (2007); Guan & Hu (2008) and Zyserman et al (2010). A wide range of field and laboratory measurements of the coseismic and interface response fields was presented (see e.g., Martner & Sparks, 1959;Thompson & Gist, 1993;Butler et al, 1996;Mikhailov et al, 1997;Beamish, 1999;Zhu et al, 1999;Mikhailov et al, 2000;Zhu et al, 2000;Garambois & Dietrich, 2001;Zhu & Toksöz, 2003, 2005Block & Harris, 2006;Bordes et al, 2006;Dupuis & Butler, 2006;Haines et al, 2007;Dupuis et al, 2007;Strahser et al, 2007;Liu et al, 2008;Zhu et al, 2008a,b;Dupuis et al, 2009). Zhu & Toksöz (2005) and Bordes et al (2006Bordes et al ( , 2008 reported on coseismic magnetic field measurements associated with a Stoneley wave and a shear wave, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations